2012
DOI: 10.1371/journal.pone.0047360
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone Rescues Dot1a-Af9-Mediated Repression of Endothelin-1 and Improves Kidney Injury in Streptozotocin-Induced Diabetic Rats

Abstract: The molecular mechanism linking aldosterone and endothelin-1 in the development of diabetic nephropathy has not been completely elucidated. Here, we provide evidence showing that streptozotocin-induced diabetic rats have significantly increased aldosterone and endothelin-1 in the kidney tissue and markedly decreased expression of Dot1a and Af9. Blocking aldosterone with spironolactone significantly reduced proteinuria, glomerulosclerosis, tubulointerstitial injury and endothelin-1 expression, and significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Our current study adds Atp6v1b1 to the growing list of Dot1a target genes including αENaC, endothelin-1, and Aqp5 [18, 24, 31]. Our previous studies have shown that Af9 recruits Dot1a to the specific subregions of αENaC promoter [32].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our current study adds Atp6v1b1 to the growing list of Dot1a target genes including αENaC, endothelin-1, and Aqp5 [18, 24, 31]. Our previous studies have shown that Af9 recruits Dot1a to the specific subregions of αENaC promoter [32].…”
Section: Discussionmentioning
confidence: 91%
“…ChIP coupled with deep sequencing (ChIP-seq) in human CD4+ T cells established a slight correlation between H3m1K79 and gene activation, a more close association of H3m3K79 with gene repression, and no correlation of H3m2K79 with transcriptional status [43]. Unlike genome-wide analyses, our gene-specific ChIP studies were focused on the upstream regions extending into the first exons of the genes examined including αENaC [16, 24, 44], Edn1 [31], Aqp5 [18], and Atp6v1b1 (Figure 6). We consistently found that Dot1l and H3m2K79 were specifically located in the regions examined.…”
Section: Discussionmentioning
confidence: 99%
“…DOT1L was shown to positively regulate GATA2 expression, 33 which is known to regulate the transcription of endothelial cell-specific genes. 34 In particular, DOT1L was shown to be negatively correlated with endothelin-1, 35 which has an important role in vasospasm and vasoconstriction. Additionally, the binding capacity of AP3D1 was found to be regulated by angiotensinogen, 36 suggesting that AP3D1 might be related to atherosclerosis in concert with a potent atherosclerotic substrate, angiotensin II.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian DOT1L plays key roles in embryogenesis, hematopoiesis, heart function, kidney function, and in MLL-related leukemogenesis 23 . In addition to its roles in the control of ENaC in the collecting duct, intriguing new data has implicated Dot1 in the control of collecting duct water channel 25 and endothelin expression 26 , and mesangial cell connective tissue growth factor expression 27 .…”
Section: Introductionmentioning
confidence: 99%